PENGARUH PERGERAKAN MEANDER TERHADAP KESEIMBANGAN ALUR SUNGAI - Siti Murniningsih (Universitas Trisakti, 2018)
Most of the river in Indonesia has a meander area especially located at the lower reach. Since the pattern of the community behaviour in Indonesia, people live in surrounding or along the river while the river plains and delta consist of alluvial soils, thus, meander migration usually occurs as a response to natural or manmade disturbances of the fluvial system. Meander River in urban area usually encourage sediment transport problem such as riverbed aggradations at the area surrounding inside of the bank then will decrease the river capacity in retaining flood while simultaneously eroding on the outer banks of meander bends. Regarding velocity distribution at the channel cross section, the minimum velocity is occurring on the inside of the meander, therefore some of the sediment loads is deposited. Related with the phenomena, protection against sedimentation and erosion along meandering river extremely needed. Previously, river adjustment within meander area are continually being made, therefore, eventually the gradient of a stream is altered to accommodate the volume of water and the velocity necessary to transport the sediment load. In this paper,understanding of various phenomenon’s in the meander area due to the sedimentation processes are described and propose the new concept of protection with low impact development (LID) approach.